2017
DOI: 10.1108/ijebr-07-2016-0205
|View full text |Cite
|
Sign up to set email alerts
|

The power of peers

Abstract: Purpose Although the role of creativity in the entrepreneurial process has long been analysed, only recently scholars have begun addressing its influence on entrepreneurial intentions, showing that complex dynamics characterise this relationship. The purpose of this paper is to understand the surrounding mechanisms (moderation and mediation) that connect creativity to entrepreneurial intentions, with a focus on social context and entrepreneurial self-efficacy. Design/methodology/approach A structured questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(44 citation statements)
references
References 105 publications
4
32
0
1
Order By: Relevance
“…Other studies have shown a direct effect of creativity on entrepreneurial intention (Zampetakis & Moustakis, 2006). Recent research has indicated that the dynamics of this are more complex, existing other variables to account for (Bellò et al, 2018;Biraglia & Kadile, 2017).…”
Section: Creativitymentioning
confidence: 96%
See 2 more Smart Citations
“…Other studies have shown a direct effect of creativity on entrepreneurial intention (Zampetakis & Moustakis, 2006). Recent research has indicated that the dynamics of this are more complex, existing other variables to account for (Bellò et al, 2018;Biraglia & Kadile, 2017).…”
Section: Creativitymentioning
confidence: 96%
“…Investigations have indicated, for example, that self-efficacy mediates variables such as risk propensity, previous entrepreneurial experience, and personality traits (Roy et al, 2017;Zhao, Seibert, & Hills, 2005). , 22(2), eRAMR210082, 2021 doi:10.1590/1678-6971/eRAMR210082 Self-efficacy has been examined as a possible mediator role between creativity and entrepreneurial intention (Bellò et al, 2018;Zampetakis, Gotsi, Andriopoulos, & Moustakis, 2011). Creativity alone may not be enough to propel the individual to undertake an entrepreneurial venture.…”
Section: Self-efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Self-efficacy is defined as a person's belief in his/her ability to complete work, achieve goals, and overcome obstacles and challenges (Bellò et al, 2017). It is an inevitable element required to start and run a business (Dardiri et al, 2019;Frunzaru & Cismaru, 2018).…”
Section: Influence Of Self-efficacy On Entrepreneurial Interestmentioning
confidence: 99%
“…[36] Sun, et al, (2016) found that entrepreneurship education had an effect on attitudes, social norms, self-efficacy and entrepreneurial intentions. [37] Education can develop and improve one's self-efficacy (UNCTAD, 2010). [38] Gradually acquired through education, self-efficacy significantly increases the level and content of personal aspirations, goals and decisions of people (Bandura et al, 2001).…”
Section: Entrepreneurship Education (Ee)mentioning
confidence: 99%